2020
DOI: 10.15324/kjcls.2020.52.2.98
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Alloimmunization and Autoimmunization in Multi-Transfused Thalassemia Patients in Sulaymaniyah Province-Iraq

Abstract: Thalassemias are considered important health issues throughout Iraq, involving its Kurdistan region. This disorder, particularly its major form, needs lifelong regular transfusions. But this form of medical care is associated with various complications including red cell alloimmunization and autoimmunization. This study determined the frequency and associations of alloimmunization among multi-transfused patients with -thalassemia major. The subjects were 204 patients who were registered at a thalassemia care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The current study’s findings also reported no significant median difference in age at the time of diagnosis of thalassemia, age at the time of the first transfusion, the total number of transfusions, and the number of hospitalizations in patients with and without alloimmunization. Abdulqader et al 22 also reported somewhat similar findings in their study.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The current study’s findings also reported no significant median difference in age at the time of diagnosis of thalassemia, age at the time of the first transfusion, the total number of transfusions, and the number of hospitalizations in patients with and without alloimmunization. Abdulqader et al 22 also reported somewhat similar findings in their study.…”
Section: Discussionsupporting
confidence: 80%
“…The median age at the time of diagnosis, age at the time of the first transfusion, the total number of transfusions, and the number of hospitalization due to thalassemia was found to be 8 (4-16) months, 20 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) months, 64 (26-127), and 4 (3-4) respectively (Table 2). There were 10 (11.9%) patients in whom splenectomy was observed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti‐Mia, anti‐E, and cold antibodies were the most frequent alloantibodies in our population, which is similar in the Eastern area 13,19–22 . However, anti‐K, one of the common alloantibodies in other areas, is not common in our population 7,12,23 …”
Section: Discussionsupporting
confidence: 51%